Covid-19 and socioeconomic crises in Africa: Overview of the prevailing incidents - Fisayo Fagbemi; Simplice Asongu (African Governance and Development Institute (AGDI), 2020)
The study gives an overview of the socio-economic consequences and implications of the COVID- 19 outbreak in Africa. While it is of common knowledge that the damage caused by the pandemic to the global economy is real, the existing socio-economic crises in Africa could further degenerate. What remains salient is that the huge economic costs would be borne by regions bereft of strong institutional regulatory setup and proactive approach to effectively ameliorate the impact of the outbreak, in both short-run and long-run, to bounce back in relation to the magnitude of the shocks suffered. It is indeed affirmed that in most sub-Saharan African (SSA) countries, such resilient measures seem to be absent or nonexistent. Given the degree of behavioral responses and attendant vulnerabilities generated, African socio-economic problems may be potentially exacerbated with the majority of the population facing severe hardships in the continent.
Keywords: 330; Socioeconomic crisis; economic risk; COVID-19; Africa